2013
DOI: 10.1136/eb-2013-101272
|View full text |Cite
|
Sign up to set email alerts
|

Comparing data accuracy between structured abstracts and full-text journal articles: implications in their use for informing clinical decisions

Abstract: The inaccuracies do not seem to affect the conclusion and interpretation overall. Structured abstracts appear to be informative and may be useful to practitioners as a resource for guiding clinical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…[18][19][20][21] This is especially prevalent in lowresource regions of the world where full-text articles may not be available whereas abstracts are. Smartphones and the ubiquitous mobile internet have contributed further to the device's popularity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] This is especially prevalent in lowresource regions of the world where full-text articles may not be available whereas abstracts are. Smartphones and the ubiquitous mobile internet have contributed further to the device's popularity.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons made between full-text articles and abstracts have shown that abstracts may contain inaccuracies, but these were minor errors and did not seem to affect the clinical bottom line. 18 Search tools, such as Consensus Abstracts, have been developed to present abstracts and TBLs assembled and viewed together for convenient reading and also to improve their validity. 10 Although the modified PubMed4Hh interface allows users to view TBLs and abstracts, and provides links back to the full-text articles in PubMed Central and publishers' sites, we are only able to compare the participants' scores and feedback for TBLs and abstracts because tracking full-text preferences is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Third, variations in the length of abstract and inaccuracy in the content of the abstract might potentially influence our results. [22] …”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by Fontelo et al (2013), "structured abstracts appear to be informative." One of the metrics considering document structure is BM25F (Robertson et al, 2004) which is a field-based extension of Okapi's BM25 widely used in information retrieval.…”
Section: Automatic Metrics For Summary Evaluationmentioning
confidence: 99%
“…The abstract has been the subject of many research projects, including attempts to evaluate their quality (Narine et al, 1991;Timmer et al, 2003;Sharma and Harrison, 2006;Prasad et al, 2012;Fontelo et al, 2013). In the past two decades, researchers have carried out a number of studies on structured abstracts from different perspectives, and compared abstracts in biomedical journals with those from social sciences journals (see review of James Hartley's research on structured abstracts; Zhang and Liu, 2011).…”
Section: Introductionmentioning
confidence: 99%